2020
DOI: 10.1055/a-1176-1884
|View full text |Cite
|
Sign up to set email alerts
|

Daucosterol linolenate from Sweet Potato Suppresses MCF7-Xenograft-Tumor Growth through Regulating PI3K/AKT Pathway

Abstract: Sweet potato is a functional food with potential antitumor properties, but the bioactive constituents and biological mechanisms remain unclear. In this study, we investigated the antitumor effect of daucosterol linolenate extracted from sweet potato and its potential mechanism. An MTT assay indicated that DLA inhibited the proliferation of breast cancer MCF-7 cells but had only weak effects on the proliferation of MDA-MB-231, 4T1, and MCF-10A cells. Flow cytometry analysis revealed that daucosterol linolenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Sweet potato (Ipomoea batatas) is a kind of both edible and medicinal agricultural food, which provides a dietary source of vitamins, minerals, carbohydrates, proteins, anthocyanins, essential fatty acids, trace elements, and other nutrients, and these active substances play roles in many pharmacological activities such as antitumor, immune regulation, hepatoprotective effect, hypoglycemic effect, hypolipidemic effect, antiaging, intestinal regulation, , antiobesity, antifatigue, and so on . Some water-soluble bioactive polysaccharides and alkali-soluble bioactive polysaccharides have been purified from purple sweet potato. In our recent report, a new 18.3 kDa homogeneous polysaccharide component named PSPP-1 was isolated from purple sweet potato, and its structures were elucidated comprehensively for the first time, which was very useful for its further structure–activity relationship study.…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato (Ipomoea batatas) is a kind of both edible and medicinal agricultural food, which provides a dietary source of vitamins, minerals, carbohydrates, proteins, anthocyanins, essential fatty acids, trace elements, and other nutrients, and these active substances play roles in many pharmacological activities such as antitumor, immune regulation, hepatoprotective effect, hypoglycemic effect, hypolipidemic effect, antiaging, intestinal regulation, , antiobesity, antifatigue, and so on . Some water-soluble bioactive polysaccharides and alkali-soluble bioactive polysaccharides have been purified from purple sweet potato. In our recent report, a new 18.3 kDa homogeneous polysaccharide component named PSPP-1 was isolated from purple sweet potato, and its structures were elucidated comprehensively for the first time, which was very useful for its further structure–activity relationship study.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 44 ] found that daucosterol can protect cells and reduce apoptosis by inhibiting the PI3K-Akt-mTOR signaling pathway. Han [ 32 , 45 ] found that daucosterol can inhibit tumor growth by affecting the PI3K-Akt-mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%